Transformation model of e-service quality: theoretical substantiation - N. Sh. Vatolkina (Вестник Российского экономического университета имени Г. В. Плеханова)
The article deals with the problem of modeling the quality of e-services on the basis of evolution analysis and comparison of object factors of theories of technologies’ adoption and continuous use. The author identified and systematized factors of technology adoption in view of consumer characteristics of the service and showed the cyclic nature of model development, when from complicated composition of factors in initial models of technology diffusion and the theory of intellectual acts through simplified ideas of factors in the theory of technology adoption the shift to current complex multi-level models was accomplished. The analysis of theories of technology continuous use showed that they were based on traditional categories of quality, expectations, perception and satisfaction of customer, as well as on the phenomenon of intentions to continue the use, which is applied in the theory of marketing. The analysis gave the author an opportunity to find the necessity to study the essence and features of eservices on the basis of modeling the start and pilot quality of e-services. Such approach helps answer the questions, which usually are not studied in quality management: which characteristics of service are important for customer to make a decision about its use and how his/her ideas about elements of service quality are transformed with acquiring experience of its use. Start quality of e-services, in our opinion, is a totality of e-service characteristics, which influence customer’s expectations concerning its ability to meet his/her needs before customer gets a factual experience of the service use. Start quality impacts the decision about using the e-service. Experience quality means the ability of e-service to meet the changing needs of customer in the process or after its use, which affects satisfaction and intention to continue the use of the e-service. The author put forward the model correlating start and experience quality of e-services.